Asatkāryavāda in āyurveda: A Critical Exploration of Its Evidences and Applications. - K, Kavya; Puranik, Subramanya; R, Darshini; Gaddala, Baburao; M R, Jeyaprakash; S, Nydile; A, Sathisha; K M, Anil Kumar; Kumar B G, Chethan (Journal of Neonatal Surgery, 2025)
In traditional Vedic India medicine was a very well developed physical science, at the same time as philosophical systems like Sāṁkhya, Nyāya, and Vaiśeṣika darśhana’s which developed basic theories of causation and reality. Āyurveda which was influenced by these darśanas mainly aligns with the Sāṁkhya doctrine of Satkāryavāda which is the view that the effect preexists in its cause. But also we see in āyurveda and in clinical practice ideas which play out as per Asatkāryavāda the Nyāya Vaiśeṣika theory which puts forth that the effect is a new production (I.e. Ārambha) and does not exist in its cause before hand. This study critically examines classical Ayurvedic evidences supporting Asatkāryavāda, particularly within the Bṛhattrayī. Concepts such as garbha formation, vikṛti viśama-samavāya, prabhāva, rasa-utpatti, and transformations through saṃskāra demonstrate emergent effects, indicating the operational relevance of Asatkāryavāda within Ayurvedic practice